Lyapunov-type inequality for a fractional boundary value problem with natural conditions - Guezane-Lakoud, Assia (2018)
We derive a new Lyapunov type inequality for a boundary value problem involving both left Riemann–Liouville and right Caputo fractional derivatives in presence of natural conditions. Application to the corresponding eigenvalue problem is also discussed.